CGRP release in an experimental human trigeminal pain model - Frese, Achim; Summ, Oliver; Evers, Stefan (Cephalalgia, 2021)
Background Migraine and trigemino-autonomic cephalalgia attacks are associated with an increase of α-calcitonin-gene related peptide levels in the ipsilateral jugular vein. It is however unknown whether trigeminal pain stimulation in healthy subjects without headache disorders also induces increase of calcitonin-gene related peptide levels. Findings We measured α-calcitonin-gene related peptide levels in eight healthy subjects after subcutaneous injection of capsaicin in the forehead and in the mandibular region and after injection of sodium chloride in the forehead. We observed a significant increase of α-calcitonin-gene related peptide level only after injection of capsaicin in the forehead (i.e. first trigeminal branch). We also observed trigemino-autonomic activation (lacrimation, rhinorrhea etc.) only after injection of capsaicin in the forehead. Conclusion Increase of α-calcitonin-gene related peptide levels do not only occur in primary headache attacks but also after experimental trigeminal pain of the first branch. This finding suggests that α-calcitonin-gene related peptide elevation is, at least an additional, unspecific effect of first trigeminal branch stimulation following pain activation and not a specific mechanism of idiopathic headache disorders.